Market Entry Strategy of Skoda-Auto into the United States - Procházka, Filip; Bolotov, Ilya; Král, Petr, 1979-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2018)
Czech Automobile manufacturer Škoda Auto has gone through dramatic development upon its acquisition by German Volkswagen Group in 1990. Since then Škoda grew exponentially and throughout previous years the automaker witnessed a monumental boom marked by two-digit annual sales growth rate, extension of its product portfolio by trending SUV type models and, ultimately, by becoming 2017’s second most profitable automaker by margin of the now eight-brand Volkswagen Group. Škoda’s popularity outgrew the European markets and the company raises its presence and share in Asian countries. Its entry to the American market has been wildly discussed by general public as well as media, especially following company’s secret registration of its trademarks in the US, but Škoda never confirmed nor disconfirmed these speculations. The aim of this thesis is to clarify whether entering the American automotive market would be feasible for the company and the entire Volkswagen Group, as well as to investigate and elaborate Škoda's potential on the US market and its appropriate market entry solution, whilst considering all major circumstances that might affect such action.
Vedoucí práce: Ilya Bolotov
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: arts management [obor dipl. práce]; diplomové práce; master's theses